POLITIK HUKUM PEMBENTUKAN KOMISI KEBENARAN DAN REKONSILIASI ACEH: RE-FORMULASI LEGALITAS KKR ACEH - Zaki Ulya (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2017)
The establishment of a Truth and Reconciliation Commission in Aceh is based on Article 229 of Law No. 11 of 2006, then legalized in Qanun No. 17 of 2013. The existence of Aceh's Truth and Reconciliation Commission has further provoked a polemic after the Governor of Aceh appointed several members of the Aceh Truth and Reconciliation Commission based on the Decree of the Governor of Aceh Number 162/796/2016. The pros and cons concerning the dissolution of the Aceh Truth and Reconciliation Commission flourished as the assessment of the Aceh Truth and Reconciliation Commission was established after the abolition of the provisions of the National Commission for Truth and Reconciliation by the Constitutional Court. This paper intends to examine the legality of the Aceh Truth and Reconciliation Commission in terms of legal and legal aspects of the existence of the Aceh TRC according to the laws and regulations. Abstrak: Pembentukan KKR di Aceh didasarkan pada Pasal 229 Undang-Undang No. 11 Tahun 2006, kemudian dilegalkan dalam Qanun No. 17 Tahun 2013. Keberadaan KKR Aceh makin menimbulkan polemik setelah Gubernur Aceh mengangkat beberapa anggota KKR Aceh berdasarkan pada Surat Keputusan Gubernur Aceh Nomor 162/796/2016. Pro dan kontra mengenai pembubaran KKR Aceh berkembang akibat penilaian KKR Aceh dibentuk setelah dihapuskannya ketentuan KKR Nasional oleh Mahkamah Konstitusi. Tulisan ini hendak mengkaji mengenai legalitas KKR Aceh ditinjau dari aspek politik hukum dan formulasi hukum mengenai keberadaan KKR Aceh menurut peraturan perundang-undangan. Kata kunci: Politik hukum, Pembentukan, KKR Aceh